Pengaruh efektivitas sistem pengendalian internal, keadilan organisasi, dan implementasi good governance terhadap kecenderungan kecurangan akuntansi pada OPD Kabupaten Jombang - Rizqia, Laela; Widajantie, Tituk Diah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine and prove the effect of the effectiveness of internal controls system, organizational justice, and good governance practices against trends in accounting fraud in OPD Jombang Regency. Accounting fraud must be followed up properly because it can have an impact on services to the community and hinder regional development. This type of research is quantitative research. The source of information in this study is the primary source of information by conducting research and distributing questionnaires. The research sample was taken using purposive sampling technique with a total of 81 respondents. Information analysis method used is multiple regression analysis method. The hypothesis tester uses a statistical test tool, namely Partial Least Square (PLS) with the help of WarpPLS 8.0 programming. The results showed that the effectiveness of the internal control system and organizational justice had a significant effect on the tendency of accounting fraud. Meanwhile, the implementation of good governance has no significant effect on the tendency of accounting fraud.